2016
DOI: 10.1371/journal.pone.0159095
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Bone Marrow-Derived Mesenchymal Stem Cells Modulate Molecular Markers of Inflammation in Dogs with Cruciate Ligament Rupture

Abstract: Mid-substance rupture of the canine cranial cruciate ligament rupture (CR) and associated stifle osteoarthritis (OA) is an important veterinary health problem. CR causes stifle joint instability and contralateral CR often develops. The dog is an important model for human anterior cruciate ligament (ACL) rupture, where rupture of graft repair or the contralateral ACL is also common. This suggests that both genetic and environmental factors may increase ligament rupture risk. We investigated use of bone marrow-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 58 publications
0
30
0
4
Order By: Relevance
“…All these in vivo studies support their therapeutic potential, although variably Hall, Rosenkrantz, Hong, Griffin, & Mendelsohn, 2010;Kim et al, 2011;Muir et al, 2016;Sousa et al, 2011). Majority of the studies have not reported any major adverse effect (Black et al, 2007(Black et al, , 2008Cuervo et al, 2014;Pérez-Merino, Usón-Casaús, Zaragoza-Bayle, et al 2015a;Bçrziòð et al, 2018;Villatoro et al, 2015), except for few studies wherein reactions like selfcontrollable localized inflammation and pulmonary parenchymal edema and hemorrhage have been reported (Kang & Park, 2014;Mokbel et al, 2011;Park et al, 2012b).…”
Section: In Vivo Potential Therapeutic Applicationsmentioning
confidence: 98%
See 1 more Smart Citation
“…All these in vivo studies support their therapeutic potential, although variably Hall, Rosenkrantz, Hong, Griffin, & Mendelsohn, 2010;Kim et al, 2011;Muir et al, 2016;Sousa et al, 2011). Majority of the studies have not reported any major adverse effect (Black et al, 2007(Black et al, , 2008Cuervo et al, 2014;Pérez-Merino, Usón-Casaús, Zaragoza-Bayle, et al 2015a;Bçrziòð et al, 2018;Villatoro et al, 2015), except for few studies wherein reactions like selfcontrollable localized inflammation and pulmonary parenchymal edema and hemorrhage have been reported (Kang & Park, 2014;Mokbel et al, 2011;Park et al, 2012b).…”
Section: In Vivo Potential Therapeutic Applicationsmentioning
confidence: 98%
“…Cranial cruciate ligament (CCL) rupture represents one of the most common causes of hindlimb lameness and the most common stifle joint disease in dogs (Johnson, Austin, & Breur, 1994). Although variable but an overall improvement in the repair has been reported with MSCs (Canapp, Leasure, Cox, Ibrahim, & Carr, 2016;Muir et al, 2016). dBM-MSCs implanted intra-articularly engraft cranial cruciate ligament and thus, may have effective role to play (Linon, Spreng, Rytz, & Forterre, 2014).…”
Section: Ligaments/tendon Injuriesmentioning
confidence: 99%
“…Macrophage polarization, both in vitro and in vivo, can be induced by mesenchymal stromal/stem cell (MSC) paracrine activity . In mammalian models of ligament or tendon healing, MSC treatments increased the presence of endogenous M2 macrophages and associated anti‐inflammatory cytokines, which subsequently resulted in improved tendon and ligament healing . We previously reported that MSCs uniquely educate macrophages toward an anti‐inflammatory phenotype (MSC‐educated macrophages [MEMs]) .…”
Section: Introductionmentioning
confidence: 99%
“…Notably, eleven dogs had Synovial:Serum CRP above 0.2 in the partial CR stifle, suggesting elevated risk of subsequent contralateral rupture [32]. …”
Section: Resultsmentioning
confidence: 99%